An Unusual Cause of Acute Pancreatitis in a Liver Transplant Recipient. Issue 5 (27th April 2021) - Nizamuddin, Imran; Kourkoumpetis, Themistoklis; Wood, Cecil G.; Levitsky, Josh
Abstract : Posttransplant lymphoproliferative disorder (PTLD) in liver transplant recipients is relatively uncommon, with an estimated incidence of 1%–3%. Retrospective reviews of liver transplant recipients have mainly reported posttransplant lymphoproliferative disorder affecting the liver, gastrointestinal tract, or lymph nodes. In this case report, we describe a 45-y-old female with a history of deceased donor liver transplantation for autoimmune hepatitis who had recurrent hospital admissions for acute pancreatitis. Ultimately, imaging revealed numerous complex pancreatic and peripancreatic masses, appearing to originate from pancreatic lymphoid tissue. Tissue biopsy later confirmed monomorphic Epstein-Barr virus-negative large B-cell lymphoma. Overall, PTLD involving the pancreas after liver transplantation is incredibly rare. The patient's cumulative immunosuppression drug dose and time posttransplant were suspected to be her main risk factors, given that she had been exposed to several years of treatment with tacrolimus, azathioprine, mycophenolate mofetil, and prednisone. She was treated with rituximab monotherapy and later escalated to chemoimmunotherapy due to lack of response. PTLD involving the pancreas is an unusual cause of pancreatitis and should be considered in cases of recurrent pancreatitis in transplant recipients.